Interlocuções entre Fiódor Dostoiévski e a psicologia analítica: uma análise do processo de individuação na obra Crime e castigo - Nosek, Deborah (2015)
The Crime and Punishment book's analysis intends to clarify reflections of the chosen literary work through a Jungian approach, which aims to reveal the path taken by the main character, Raskólnikov, in his search of totality. This theme’s choice occurred by the desire to investigate how such a process can be expressed in mankind’s issues and elucidates its psychological value within the novel. Under an analytical understanding, this research shows the assimilation of the marginalized acts and the elaboration of these contents, pondering about the importance of recognizing the dark parts that are common to all individuals. Expand the perspective of the individuation process leads to a different kind of reaction concerning the different stages of it. The psyche’s compensatory mechanism expresses the need for harmonious match between the person’s contradictory characteristics. In this sense, it illustrates the potential hidden behind less estimated assignments. Once aware of this way of human functioning, people tend to be lead to superior understanding and therefore greater empathy for those who experience it in harder ways. Thereby, it becomes possible for individuals to free up themselves from their own incarceration and self inflicted punishment. It is noticed that the very existence is vulnerable to failures and fears, but also prone to creativity and planning